Comparison of Outcomes of Dialectical Behavior Therapy (DBT) Alone versus DBT Combined with Second-Generation Antipsychotic in the Treatment of Borderline Personality Disorder - Ijaz, Mudassar; Ishaq, Sana; Siraj, Syeda Areeba; Sarwar, Adnan; Mujtaba, Muhammad; Chandar, Subash (Indus Journal of Bioscience Research, 2025)
Background: Borderline Personality Disorder (BPD) is a complex psychiatric condition characterized by emotional instability, impulsivity, self-harming behaviors, and difficulties in interpersonal relationships. While Dialectical Behavior Therapy (DBT) is widely recognized as the most effective treatment for BPD, some individuals continue to struggle with severe mood disturbances and impulsive behaviors, necessitating additional therapeutic interventions. This study aimed to compare the outcomes of DBT alone versus DBT combined with second-generation antipsychotic medication (olanzapine) in the treatment of BPD. Methodology: A randomized controlled trial was conducted at Gulab Devi Hospital, Lahore, where 102 participants diagnosed with BPD, as per DSM-5 criteria, were recruited and assigned to one of two treatment groups. Group A received DBT alone, while Group B received DBT along with olanzapine (5-20 mg/day). Treatment effectiveness was assessed using standardized clinical scales, including the Hamilton Depression Rating Scale (HAM-D), Hamilton Anxiety Rating Scale (HARS), and Barratt Impulsiveness Scale (BIS-11). Additionally, self-harm attempts and emergency unit visits were recorded over a 12-week period. Result: The results indicated that both groups showed significant symptom reduction; however, the DBT + Olanzapine group demonstrated greater improvements across all measured outcomes. Participants in the combination therapy group exhibited significantly lower post-treatment scores for depression, anxiety, and impulsivity compared to the DBT-alone group (p < 0.05). Moreover, there was a notable reduction in self-harm attempts and emergency visits in the DBT + Olanzapine group, suggesting enhanced emotional stabilization and crisis prevention. Conclusion: These findings support the potential benefits of combining DBT with pharmacological intervention in the management of BPD, particularly for individuals with severe emotional dysregulation and high-risk behaviors. However, given the side effect profile of olanzapine, individualized treatment plans should be considered. Further research with long-term follow-up is needed to assess the sustainability of treatment effects and medication adherence.